Face Masks Impact Auditory and Audiovisual Consonant Recognition in Children With and Without Hearing Loss - Lalonde, Kaylah; Buss, Emily; Miller, Margaret K.; Leibold, Lori J. (Frontiers in Psychology, 2022)
Teachers and students are wearing face masks in many classrooms to limit the spread of the coronavirus. Face masks disrupt speech understanding by concealing lipreading cues and reducing transmission of high frequency acoustic speech content. Transparent masks provide greater access to visual speech cues than opaque masks but tend to cause greater acoustic attenuation. This study examined the effects of four types of face masks on auditory-only and audiovisual speech recognition in 18 children with bilateral hearing loss, 16 children with normal hearing, and 38 adults with normal hearing tested in their homes, as well as 15 adults with normal hearing tested in the lab. Stimuli simulated the acoustic attenuation and visual obstruction caused by four different face masks: hospital, fabric, and two transparent masks. Participants tested in their homes completed auditory-only and audiovisual consonant recognition tests in speech-spectrum noise at 0 dB SNR. Adults tested in the lab completed the same tests at 0 and/or -10 dB SNR. A subset of participants from each group completed a visual-only consonant recognition test with no mask. Consonant recognition accuracy and transmission of three phonetic features (place of articulation, manner of articulation, and voicing) were analyzed using linear mixed effects models. Children with hearing loss identified consonants less accurately than children and adults with normal hearing tested at 0 dB SNR. However, all groups were similarly impacted by face masks. In auditory-only conditions, results were consistent with the pattern of high frequency acoustic attenuation; the hospital mask had the least impact on performance. High frequency attenuation had the greatest impact on place perception and the least impact on voicing perception. In audiovisual conditions, the transparent masks had less impact on performance than the opaque masks. Differences between transparent and opaque masks were larger for place perception than voicing and manner perception, a finding consistent with the visual-only feature transmission data. These results suggest that the combination of noise and face masks negatively impacts speech understanding in children, and that the best masks for promoting speech understanding in noisy environments depends on whether visual cues will be accessible.